Sequencing effects of small-sided games and high-intensity interval training on physical and physiological performance of young soccer players during pre-season - Kharatzadeh, Masoud (2025)
Study aim: This experimental study investigated the sequencing effects of a small-sided games (SSG) protocol and high intensity interval training (HIIT) on the physical and physiological performance adaptation of soccer players, conducted over a fourteen-week of the pre-season. Materials and methods: Twenty-three young (aged 14 ±0.1 years) male soccer players from a club participating in national level competitions were randomly divided into two groups (SSG + HIIT, n = 11 and HIIT + SSG, n = 12). The first group completed SSGs (5 vs. 5 + goalkeeper, 36 × 30 m) followed by HIIT (long interval at 60 to 75% of final velocity during 30–15 intermittent fitness test) training, while the second group performed HIIT training and then SSGs. Assessments were conducted at baseline and post-intervention for 10 m linear sprint, body fat percentage, countermovement jump (CMJ), change of direc tion speed (CODS), squat jump (SJ), and Yo-Yo intermittent recovery test (Yo-Yo IR). Results: A significant main effect of time was reported for 10 m linear sprint, CMJ, CODS, SJ, and Yo-Yo IR (p ≤ 0.001–0.010, ηp 2 = 0.32–0.74). However, no significant group × time interaction were reported for any dependent variables (p = 0.433–1.000, ηp 2 ≤ 0.01–0.03). Conclusion: The sequencing order of HIIT and SSG does not affect the performance outcomes in young male soccer players. Moreover, similar improvements can be expected in the 10 m linear sprint, CMJ, CODS, SJ, and Yo-Yo IR, irrespective of the exercise order. However, caution should be taken when interpreting the within-group improvements, as the study did not include a control group.